Regulation of Pattern-Recognition Receptor Signaling by HBX During Hepatitis B Virus Infection - You, Hongjuan; Qin, Suping; Zhang, Fulong; Hu, Wei; Li, Xiaocui; Liu, Dongsheng; Kong, Fanyun; Pan, Xiucheng; Zheng, Kuiyang; Tang, Renxian (Frontiers in Immunology, 2022)
As a small DNA virus, hepatitis B virus (HBV) plays a pivotal role in the development of various liver diseases, including hepatitis, cirrhosis, and liver cancer. Among the molecules encoded by this virus, the HBV X protein (HBX) is a viral transactivator that plays a vital role in HBV replication and virus-associated diseases. Accumulating evidence so far indicates that pattern recognition receptors (PRRs) are at the front-line of the host defense responses to restrict the virus by inducing the expression of interferons and various inflammatory factors. However, depending on HBX, the virus can control PRR signaling by modulating the expression and activity of essential molecules involved in the toll-like receptor (TLR), retinoic acid inducible gene I (RIG-I)-like receptor (RLR), and NOD-like receptor (NLR) signaling pathways, to not only facilitate HBV replication, but also promote the development of viral diseases. In this review, we provide an overview of the mechanisms that are linked to the regulation of PRR signaling mediated by HBX to inhibit innate immunity, regulation of viral propagation, virus-induced inflammation, and hepatocarcinogenesis. Given the importance of PRRs in the control of HBV replication, we propose that a comprehensive understanding of the modulation of cellular factors involved in PRR signaling induced by the viral protein may open new avenues for the treatment of HBV infection.